Management of anterior cruciate ligament injuries in skeletally immature individuals - Moksnes, H.; Engebretsen, L.; Risberg, M. A. (Journal of Orthopaedic & Sports Physical Therapy, 2012)
Anterior cruciate ligament (ACL) injuries in skeletally immature individuals remain a challenge for the child, the parents, orthopaedic surgeons, and physical therapists. The main challenges are the potential risk of recurrent instability, secondary injuries following nonoperative treatment, and the risks involved with surgical treatment due to the vulnerability of the epiphyseal growth plates. We first present the physiological background for considerations that must be made when advising on treatment alternatives for skeletally immature individuals after ACL injury. The implications of continuous musculoskeletal development for treatment decisions are emphasized. No randomized controlled trials have been performed to investigate outcomes of different treatment algorithms. There is no consensus in the literature on clinical treatment decision criteria for whether a skeletally immature child should undergo transphyseal ACL reconstruction, physeal sparing ACL reconstruction, or nonoperative treatment. Additionally, well-described rehabilitation programs designed for either nonoperative treatment or postoperative rehabilitation have not been published. Based on the currently available evidence, we propose a treatment algorithm for the management of ACL injuries in skeletally immature individuals. Finally, we suggest directions for future prospective studies, which should include development of valid and reliable outcome measures and specific rehabilitation programs.